2015
DOI: 10.1523/jneurosci.3454-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Subventricular Zone Continues to Generate Corpus Callosum and Rostral Migratory Stream Astroglia in Normal Adult Mice

Abstract: Astrocytes are the most abundant cells in the CNS, and have many essential functions, including maintenance of blood-brain barrier integrity, and CNS water, ion, and glutamate homeostasis. Mammalian astrogliogenesis has generally been considered to be completed soon after birth, and to be reactivated in later life only under pathological circumstances. Here, by using genetic fate-mapping, we demonstrate that new corpus callosum astrocytes are continuously generated from nestin ϩ subventricular zone (SVZ) neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 39 publications
2
60
0
Order By: Relevance
“…Conversely, adult NSCs must be ready for both glial and neuronal lineages depending on the respective acute needs, and they remain so over a long period throughout life. In fact, NSCs in the SEZ retain the capacity to produce both oligodendrocytes and astrocyes, as well as neurons, at the adult stage under intact and injured conditions (Hack et al 2004; Menn et al 2006; Jablonska et al 2010; Benner et al 2013; Ortega et al 2013; Rafalski et al 2013; Sohn et al 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, adult NSCs must be ready for both glial and neuronal lineages depending on the respective acute needs, and they remain so over a long period throughout life. In fact, NSCs in the SEZ retain the capacity to produce both oligodendrocytes and astrocyes, as well as neurons, at the adult stage under intact and injured conditions (Hack et al 2004; Menn et al 2006; Jablonska et al 2010; Benner et al 2013; Ortega et al 2013; Rafalski et al 2013; Sohn et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Although most embryonic radial glial cells behave like neuroblasts and readily differentiate into postmitotic neurons (Qian et al 1997; Heins et al 2002; Haubst et al 2004), only some can be forced to acquire multipotency by addition of growth factors (Qian et al 2000; Gabay et al 2003; Hack et al 2004)—fully consistent with their genome-wide expression profile closely clustering to adult NBs (Beckervordersandforth et al 2010). Conversely, adult NSCs are intrinsically multipotent and can still readily undergo gliogenesis as well as neurogenesis in vivo and in vitro (Hack et al 2004; Menn et al 2006; Benner et al 2013; Ortega et al 2013; Rafalski et al 2013; Sohn et al 2015). Thus, multipotency requires lowering the levels of fate determinants for one specific fate, suggesting that the tight control of fate determinants is a key strategy for the long-term maintenance of multipotent adult NSCs.…”
Section: Going Up Instead Of Going Down—distinct Regulation Of Neurogmentioning
confidence: 99%
“…Recent work has shown that Nestin + NSCs in the V-SVZ continue to produce astrocytes in the corpus callosum and RMS in adult mice (Sohn et al, 2015). In contrast, debates regarding the existence of cortical neurogenesis in the adult brain are ongoing.…”
Section: V-svz and Other Sources Of New Neurons And Glia: Potential Fmentioning
confidence: 99%
“…Maximal astrocyte production occurs perinatally (5) from intermediate progenitors in the VZ/SVZ (38, 47), as well as from local GFAP astrocytes in other brain regions (18). VZ/SVZ (54) and local astrocyte production decreases to low levels in the young adult brain (18). Thus, adult astrocytes are terminally differentiated and essentially quiescent.…”
Section: Introductionmentioning
confidence: 99%